Analogue Sandbox Scaled Modelling of Oblique and Orthogonal Extension Rifting in Rukwa Rift Basin, Tanzania - Ojok, Tonny; Duot, John BK; Namaganda, Majorine; Sadiki , Nasra; Msabi, Michael (Tanzania Journal of Science, 2021)
Fault evolution in oblique and orthogonal rift systems in the brittle upper crust of the Rukwa rift basin was simulated using scaled sandbox modelling by varying the angle between the rift axis and the extension direction, α, through 45° and 90°, over a 10 cm displacement. The 45° oblique model exhibits a half-graben architecture bounded by a planar fault, intra-rift faults and a conjugate fault in some vertical sections. The map view of the model’s basin trends in the NW-SE direction, and is comparable with the Rukwa rift basin orientation. The 90° oblique model forms a basin structure which is orthogonal to the extension direction of the model in aerial photos. Its linear fault remains orthogonal to the extension direction, while the flexural side of the model segments into sinuous normal faults. Planar to slightly curved intra-rift faults are observed in vertical sections. The half-grabens have similar geometries in vertical sections for both models, while intra-rift faults elongate in vertical sections. The results of the oblique model are similar to natural examples of rift fault systems like the Rukwa rift. The fault geometries of the sandbox models can serve as examples for recognizing fault styles in oblique rift systems. Keywords: Analogue Sandbox modelling, Oblique rifting, Orthogonal rifting, Tanganyika-Rukwa-Malawi Rift Segment, Rukwa Rift Basin.